A three-criteria performance score for rats exercising on a running treadmill - Gabriel Rios-Kristjansson, Juan; Rizo-Roca, David; Mist Kristjansdottir, Karen; Nuñez Espinosa, Cristian Andrés; Ramon Torrella, Joan; Pages, Teresa; Viscor, Gines (My University, 2019)
In this study, we propose a novel three-criteria performance score to semiquantitatively classify the running style, the degree of involvement and compliance and the validity of electric shock count for rats exercising on a treadmill. Each score criterion has several style-marks that are based on the observational registry of male Sprague-Dawley rats running for 4-7 weeks. Each mark was given a score value that was averaged throughout a session-registry and resulting in a session score for each criterion, ranging from "0" score for a hypothetical "worst runner", to score "1" for a hypothetical "perfect runner" rat. We found significant differences throughout a training program, thus providing evidence of sufficient sensitivity of this score to reflect the individual evolution of performance improvement in exercise capacity due to training. We hypothesize that this score could be correlated with other physiological or metabolic parameters, thus refining research results and further helping researchers to reduce the number of experimental subjects.
Keywords: Treadmill